Potential strategies for revitalizing UKM mosque in enhancing community engagement - Mohd Farid Mohamed,; Wardah Fatimah Mohammad Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2023)
UKM (Universiti Kebangsaan Malaysia) Mosque has existed in Bandar Baru Bangi for over 40 years, however, the locals’ involvement in its daily activities is still lack and has yet optimum. Thus, there is a need to revitalise UKM Mosque to be more relevant to local communities. At the same time, the mosque also requires a lot of maintenance and this incurs costs to UKM. With the recent budget cuts to universities by the Ministry of Higher Education (MoHE), as well as the Covid19 pandemic impact, the UKM Islamic Centre (UIC) has been encouraged to focus also on the income generation activities. The objective of this study is to investigate the potential of revitalizing the UKM Mosque by proposing new facilities, renovation or any appropriate improvement that could lead to a greater impact on the local communities, as well as increase the income of the mosque to be financially sustainable. The method adopted in this study is the combination of literature review, case studies, series of discussions with related parties and a questionnaires survey. The outcome of the study is a list of proposed improvements with priority given to the facilities that meet the end users’ needs, such as cafe and elevators. The list could be a useful guideline for UIC to refer to before making any decisions on future development of UKM Mosque. This study is hoped to assist UIC to generate greater income and, at the same time provide more significant and meaningful impact on the local communities.